The Longhouse [2015-] - Spiller, Neil (Architecture Image Studies, 2020)
Communicating Vessels is a self-instigated, drawn and written theoretical architectural design project. The project re-examines traditional paradigms and elements of garden design such as the gazebo, the garden shed, walled garden, bird bath, entrance gates, riverside seats, love seats, vistas, sculptures, fountains, topiary and outside grown rooms among many other objects and spaces. It redesigns them, electronically connects them, explores their virtual and actual materiality, and their cultural and mnemonic importance, and reassesses them in the wake of the impact of advanced technology on the protocols of contemporary architectural design in the twenty-first century. At the projects, centre is the Longhouse.